The requirements of junior high school/MTs mathematics teachers in Riau for integrated literacy and numeracy teaching modules aimed at enhancing students' critical mathematical thinking skills - Elfis Suanto; Kartini Kartini; Anisa Sonia (State Islamic University of North Sumatra, 2024)
The role of teachers as implementers is crucial in the execution of the Independent Curriculum. Teaching modules can serve as guidelines for teachers to ensure effective and efficient learning. Strengthening literacy and numeracy is one of the demands of the Independent Curriculum, aiming to develop students with critical mathematical thinking skills to compete globally. However, field observations indicate that teachers still require guidance in compiling teaching modules that align with the Independent Curriculum and meet their students' needs. This descriptive study analyzes teachers' needs for integrated literacy and numeracy teaching modules to enhance students' critical thinking skills. Data were collected through a non-test questionnaire distributed via Google Forms to junior high school/MTs mathematics teachers in Riau, with 11 participants. The study's results indicated that 72.7% of teachers expressed a significant need for integrated literacy and numeracy teaching modules to improve students' critical mathematical thinking abilities. Additionally, the analysis revealed that some teachers had developed their own teaching modules, but these lacked the integration of literacy and numeracy, and did not facilitate students' critical mathematical thinking skills. This highlights the necessity for the development of integrated literacy and numeracy teaching modules to enhance students' critical mathematical thinking skills.